Barriers to climate adaption in farming - KUMAR, DR. P. PRAVEEN; KUMAR. K, MR. SATHEESH (The journal of contemporary issues in business and government, 2020)
Descriptive research is applied by using a convenience method of sampling with 70 respondents. The data is collected from the farmers. The majority of respondents were both male and female and their majority of age group were less than 35 years. The tools used for the study are mean analysis, frequency analysis, t-test and ANOVA. It is found that farming is the factor influenced by climate and farming has barriers to adapt to the climate. Cultivating expects a fundamental part in the economy of non-modern countries, and gives the essential wellspring of food, pay and work to their common masses. It has gotten logically clear over the last couple of years that the start of both monetary master and system makers regarding the work of cultivation in money related improvement has experienced a huge headway. Around one fourth of the Earth's bound surface is as of now a work in progress with more land changed over to manage creation. Humanity has similarly gotten skilled at raising yields through using inputs like manures, pesticides and common waste products. Anyway in various more shocking countries with low benefit rates and creating masses, agribusiness continues wandering into immaterial and sensitive grounds. It adds to the monetary new development. In light of the public compensation level, similarly as people's lifestyle is improved.